2007
DOI: 10.1016/s0377-1237(07)80009-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Protective Footwear on Floor and Air Contamination of Intensive Care Units

Abstract: Floor and air colony counts showed no significant difference in the two phases with and without protective footwear. Protective footwear had no significant impact on bacterial contamination of floors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 5 publications
1
7
0
Order By: Relevance
“…Evaluating the exogenous effect to bacterial contamination in ICU, Gupta et al study on the impact of footwear as protective measure against contamination, the study recorded no significance difference between the contamination rate and the footwear [6] In this study, we isolated 10 different bacterial pathogens, Bacillus spp, 33.8%(n=24), S.aureus, 26.8% (n=19 ) and CoNS 19.7%(n=14), and predominate in both units, indoor contamination 51.7%(n=15)in AICU,and 47.6%(n=20) in NICU and surface items/equipments contamination 48.3%(n=14) and 35.7%(n=15) respectively. Other studies have reported the predominance of staphylococci and Bacillus spp [5,6,18,22,23,31]. The recovery of potentially clinically relevant S.aureus CoNs, E.coli,.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Evaluating the exogenous effect to bacterial contamination in ICU, Gupta et al study on the impact of footwear as protective measure against contamination, the study recorded no significance difference between the contamination rate and the footwear [6] In this study, we isolated 10 different bacterial pathogens, Bacillus spp, 33.8%(n=24), S.aureus, 26.8% (n=19 ) and CoNS 19.7%(n=14), and predominate in both units, indoor contamination 51.7%(n=15)in AICU,and 47.6%(n=20) in NICU and surface items/equipments contamination 48.3%(n=14) and 35.7%(n=15) respectively. Other studies have reported the predominance of staphylococci and Bacillus spp [5,6,18,22,23,31]. The recovery of potentially clinically relevant S.aureus CoNs, E.coli,.…”
Section: Discussionmentioning
confidence: 97%
“…Contamination occurs via cross-transmission and dissemination, occupancy density, usage of medical equipment for multiple patient like stethoscope, gowns and clothing [5][6][7][8], colonized/ infected health care worker/patient, their accessories and clinical specimens [9][10][11]. Nonadherence of health care worker to simple standard procedure of hand washing, contribute significantly to the spread of pathogens, and cross-transmission during contact with patient or contaminated inanimate surfaces [12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ecoli, pseudomonas, klebsiella and enterobacter species were sporadically isolated in their study. On an average individual sheds 10^6 squares per day (5,6) . Skin squames from patients and staff are likely to be staphylococcus epidermitis and other coagulase negative cocci and bacilli.…”
Section: Discussionmentioning
confidence: 99%
“…Such diseases can result because of different causes like advancement and determination of multidrugresistant (MDR) microbes, immune-compromised conditions of patients, and mechanical transmission of microorganisms [6]. Some non-basic therapeutic gadgets routinely utilized by healthcare workers (HCWs, for example, stethoscopes, pulse sleeves, electronic thermometers, latex gloves, covers, pens, and white coats assume a critical role in the transmission of health careassociated infections (HCAIs) [6]. Among these gadgets, stethoscopes routinely utilized by HCWs represent a potential risk for HCAIs transmission in the hospital settings [6].…”
Section: Introductionmentioning
confidence: 99%